2021
DOI: 10.20944/preprints202107.0134.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Same Brain, Different Look? – the Impact of Scanner, Sequence and Preprocessing on Diffusion Imaging Outcome Parameters

Abstract: In clinical diagnostics and longitudinal studies, the reproducibility of MRI assessments is of high importance in order to detect pathological changes, but developments in MRI hard- and software often outrun extended periods of data acquisition and analysis. This could potentially introduce artefactual changes or masking pathological alterations. However, if and how changes of MRI hardware, scanning protocols or preprocessing software affect complex neuroimaging outcomes from e.g. diffusion weighted imaging (D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Conversely, the lower the measurement variance and the more consistent observations can be made between repeated measurements, the higher the statistical power to detect effects in a study [14]. Studies examining the quality of connectome mappings by means of neuroimaging data have pointed out that connectome reconstructions can vary significantly from study to study due to motion artefacts [19], scanner quality [80] and non-neural physiological processes [81] as well as different approaches in the analysis such as atlas choice [76,82] (Figure 3e) and thresholding [23,75] (Figure 3f). Test-retest studies have reported strong differences in measurement reliability for a wide range of connectome variables, including cortical thickness between brain areas [83]; fractional anisotropy between white-matter voxels [84] (Figure 3g); structural connectivity between edges [22]; functional connectivity between resting state networks [21]; and for example local graph metrics of structural [20] and function connectivity [85].…”
Section: Variancementioning
confidence: 99%
“…Conversely, the lower the measurement variance and the more consistent observations can be made between repeated measurements, the higher the statistical power to detect effects in a study [14]. Studies examining the quality of connectome mappings by means of neuroimaging data have pointed out that connectome reconstructions can vary significantly from study to study due to motion artefacts [19], scanner quality [80] and non-neural physiological processes [81] as well as different approaches in the analysis such as atlas choice [76,82] (Figure 3e) and thresholding [23,75] (Figure 3f). Test-retest studies have reported strong differences in measurement reliability for a wide range of connectome variables, including cortical thickness between brain areas [83]; fractional anisotropy between white-matter voxels [84] (Figure 3g); structural connectivity between edges [22]; functional connectivity between resting state networks [21]; and for example local graph metrics of structural [20] and function connectivity [85].…”
Section: Variancementioning
confidence: 99%
“…To date, consistency of MRI-based WM measurements has been evaluated through numerous studies, especially for the DWI technique (Boekel et al, 2017; Grech-Sollars et al, 2015; Hakulinen et al, 2021; Magnotta et al, 2012; Teipel et al, 2011; Thieleking et al, 2021; Veenith et al, 2013). These studies reported moderate to high reliability in the WM using Intraclass correlation coefficient (ICC) or Pearson’s correlation ranging from 0.5 to >0.8 as well as within- and between-subject coefficients of variation (CV) ranging from 1 to 8% and 1 to 15% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported moderate to high reliability in the WM using Intraclass correlation coefficient (ICC) or Pearson’s correlation ranging from 0.5 to >0.8 as well as within- and between-subject coefficients of variation (CV) ranging from 1 to 8% and 1 to 15% respectively. Among DTI-derived measures, Fractional anisotropy (FA) and Mean Diffusivity (MD) generally show the highest reliability across different WM regions (Acheson et al, 2017; Hakulinen et al, 2021; Luque Laguna et al, 2020; Palacios et al, 2017; Shahim et al, 2017; Thieleking et al, 2021; Zhou et al, 2018). For NODDI-derived measures, studies reported similar (intracellular volume fraction, ICvf) or higher (orientation dispersion, OD) reliability compared to DTI measures, while isotropic volume fraction (ISOvf) showed the poorest reliability (ICC<0.6) (Andica et al, 2020; Chung et al, 2016; Granberg et al, 2017; Lucignani et al, 2021; Tariq, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation